2011
DOI: 10.1016/j.brainres.2011.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of CRF-immunoreactive neurons distribution in mouse and rat brains and selective induction of Fos in rat hypothalamic CRF neurons by abdominal surgery

Abstract: Mice and rats are widely used in stress-related behavioral studies while little is known about the distribution of the stress hormone, corticotropin-releasing factor (CRF) in the mouse brain. We developed and characterized a novel rat/mouse CRF polyclonal antibody (CURE ab 200101) that was used to detect and compare the brain distributions of CRF immunoreactivity in naïve and colchicine-treated rats and mice. We also assessed whether the visceral stressor of abdominal surgery activated brain CRF neurons using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 90 publications
2
52
1
Order By: Relevance
“…However, the CA fields contain no CRF-ir cells in the tree shrew brain. The different effects of colchicine on CRF-ir cells and fibers in different regions of tree shrews are similar to previous reports (Merchenthaler, 1984;Wang et al, 2011). For example the BST, the distribution of CRF-ir cell bodies is much enhanced with colchicine, but the fibers are hardly diminished.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, the CA fields contain no CRF-ir cells in the tree shrew brain. The different effects of colchicine on CRF-ir cells and fibers in different regions of tree shrews are similar to previous reports (Merchenthaler, 1984;Wang et al, 2011). For example the BST, the distribution of CRF-ir cell bodies is much enhanced with colchicine, but the fibers are hardly diminished.…”
Section: Discussionsupporting
confidence: 85%
“…In addition, there are different distribution patterns of positive neurons in the SCN of the tree shrew and rat brains (Sakanaka et al, 1987;Wang et al, 2011). Colchicine significantly inhibits the CRF fibers in the MEin projected from CRF neurons in the PVN.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Lee et al [27] observed an upregulation of the Slc6a3 gene due to a high-fat diet intake, a finding that runs counter to our results. In this respect, there are several studies [28,29,30], which have detected differences in the expression levels of certain genes in the brain when comparing rats and mice, indicating that there could be species-specific changes. Moreover, Vucetic et al [31] described a downregulation of Slc6a3 in the hypothalamus in offspring of dams fed a high-fat diet during pregnancy and lactation.…”
Section: Discussionmentioning
confidence: 99%
“…32,[66][67][68][69] In particular, major sites of CRF mRNA and CRF immunoreactivity are located in the paraventricular nucleus (PVN) of the hypothalamus, cerebral cortex, amygdalar-hippocampal complex and pontine Barrington's nucleus in rodents and humans. 67,68 With regards to the brain distribution of CRF receptors, dense CRF 1 receptor expression is found in the forebrain, subcortical limbic structures (more prominently in the septal region) and amygdala, whereas the expression in the hypothalamus is low under basal conditions but markedly up-regulated by stress. 32,70,71 Moreover, CRF 1 receptors at the gene and protein levels are prominently expressed in the anterior and intermediate lobe of the pituitary.…”
Section: Role Of Brain Corticotropin-releasing Factor Receptor 1 In Smentioning
confidence: 99%